Attending the Truth and Reconciliation Commission of Canada National Event in Vancouver, September 2013: a narrative report - Sutherland, Stewart; Russell, Lachlan; Adams, Michael; Baird, Rose; Shearer, Heather Kamarra; Watson, Sam (Aboriginal Studies Press, 2014)
The Truth and Reconciliation Commission of Canada (TRC) National Event in Vancouver, 18-21 September 2013, was a significant reconciliation event for First Nations peoples of Canada and the survivors of the Residential School system, which ran from the mid-to-late 1800s until 1996, when the last school was closed (Health Canada 2013). Overall, some 150,000 First Nations children passed through Residential Schools, resulting in seriously detrimental effects upon those children, as well as the subsequent generations (TRC n.d.a).